Lattice Resonances in Transdimensional WS2 Nanoantenna Arrays - Viktoriia E. Babicheva; Jerome V. Moloney (Applied Sciences, 2019)
Mie resonances in high-refractive-index nanoparticles have been known for a long time but only recently have they became actively explored for control of light in nanostructures, ultra-thin optical components, and metasurfaces. Silicon nanoparticles have been widely studied mainly because of well-established fabrication technology, and other high-index materials remain overlooked. Transition metal dichalcogenides, such as tungsten or molybdenum disulfides and diselenides, are known as van der Waals materials because of the type of force holding material layers together. Transition metal dichalcogenides possess large permittivity values in visible and infrared spectral ranges and, being patterned, can support well-defined Mie resonances. In this Communication, we show that a periodic array of tungsten disulfide (WS2) nanoantennae can be considered to be transdimensional lattice and supports different multipole resonances, which can be controlled by the lattice period. We show that lattice resonances are excited in the proximity to Rayleigh anomaly and have different spectral changes in response to variations of one or another orthogonal period. WS2 nanoantennae, their clusters, oligomers, and periodic array have the potential to be used in future nanophotonic devices with efficient light control at the nanoscale.